Exploring YidR Gene from Klebsiella pneumoniae To Design a Multi-epitope Vaccine Using Immunoinformatics Approach - Wildan Seputra, Maulana; Susiati, Hani; Raras, Tri Yudani Mardining (Graduate School, Universitas Brawijaya, 2022)
Klebsiella pneumoniae is the main leading cause of hospital-acquired infection, leading to severe infections such as pneumonia and urinary tract infection. There is an urge to develop an efficient Klebsiella vaccine, and epitope-based vaccines may offer a practical choice. Therefore, this study aims to design an epitope-based vaccine construct. YidR gene is expressed in all strains of Klebsiella with 97.6% of sequence homology, which makes it a potential vaccine candidate. In silico approach was used to make a multi-epitope vaccine construct consisting of immunogenic epitopes against the YidR gene of Klebsiella. Acquired multi-epitopes vaccine was analyzed for antigenicity, allergenicity, toxicity, and various physicochemical parameters. Molecular docking simulation was performed using TLR2 and TLR4 to asses binding affinity with the designed vaccine construct. The results showed that the predicted multi-epitope-based vaccine candidate is non-allergen, non-toxic, and has an efficient binding affinity towards TLR2 and TLR4 that could effectively induce immune responses. Keywords: In Silico, Klebsiella pneumoniae, vaccine design, YidR gene.